Potential for Assessing Dynamic Problem-Solving at the Beginning of Higher Education Studies - Csapó, Benő; Molnár, Gyöngyvér (Frontiers in Psychology, 2017)
There is a growing demand for assessment instruments which can be used in higher education, which cover a broader area of competencies than the traditional tests for disciplinary knowledge and domain-specific skills, and which measure students' most important general cognitive capabilities. Around the age of the transition from secondary to tertiary education, such assessments may serve several functions, including selecting the best-prepared candidates for certain fields of study. Dynamic problem-solving (DPS) is a good candidate for such a role, as tasks that assess it involve knowledge acquisition and knowledge utilization as well. The purpose of this study is to validate an online DPS test and to explore its potential for assessing students' DPS skills at the beginning of their higher education studies. Participants in the study were first-year students at a major Hungarian university (n = 1468). They took five tests that measured knowledge from their previous studies: Hungarian language and literature, mathematics, history, science and English as a Foreign Language (EFL). A further, sixth test based on the MicroDYN approach, assessed students' DPS skills. A brief questionnaire explored learning strategies and collected data on students' background. The testing took place at the beginning of the first semester in three 2-h sessions. Problem-solving showed relatively strong correlations with mathematics (r = 0.492) and science (r = 0.401), and moderate correlations with EFL (r = 0.227), history (r = 0.192), and Hungarian (r = 0.125). Weak but still significant correlations were found with certain learning strategies, positive correlations with elaboration strategies, and a negative correlation with memorization strategies. Significant differences were observed between male and female students; men performed significantly better in DPS than women. Results indicated the dominant role of the first phase of solving dynamic problems, as knowledge acquisition correlated more strongly with any other variable than knowledge utilization.